1987
DOI: 10.1097/00000658-198709000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Whole Pancreas and Pancreatic Islet Transplantation in Controlling Nephropathy and Metabolic Disorders of Diabetes

Abstract: To compare the long-term effectiveness of whole pancreas transplantation and pancreatic islet transplantation in controlling the metabolic disorders and preventing the kidney lesions of alloxan diabetes, metabolic and morphologic studies were performed in four groups of rats: (1) NC-116 nondiabetic controls; (2) DC-273 untreated alloxan-diabetic controls; (3) PDT-182 rats that received syngeneic pancreaticoduodenal transplants not long after induction of diabetes with alloxan; and (4) IT-92 rats that received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

1987
1987
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
0
23
0
2
Order By: Relevance
“…Several studies of islet transplantation in diabetic rats have been performed demonstrating the potential to reverse the diabetic state and associated microvascular complications (Mauer et al, 1975;Orloff et al, 1987;Schmidt 1983). One such study reported that the development of nerve fibre abnormalities could be prevented if islets were transplanted soon after the onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of islet transplantation in diabetic rats have been performed demonstrating the potential to reverse the diabetic state and associated microvascular complications (Mauer et al, 1975;Orloff et al, 1987;Schmidt 1983). One such study reported that the development of nerve fibre abnormalities could be prevented if islets were transplanted soon after the onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, optimal diabetic control remains a practical impossibility in many diabetics, since even the most meticulous form of insulin therapy cannot accurately mimic the more precise and subtle blood glucose control afforded by a working pancreas. At present this can be achieved only by the transplantation of islets of Langerhans, or whole pancreas (Orloff et al, 1987; to replace the function of the damaged beta cells.…”
Section: Introductionmentioning
confidence: 99%
“…In one study by Orloff et al [18] the initial intraportal islet graft and subsequent function may have been inadequate. In a second study by Hiller et al [19], both intraportal and renal subcapsular grafts of 1800 islets appeared to show good early function but the intraportal grafts began to fail at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have used light microscopic assessment [18], but Hirose et at. [26] have shown that light microscopic analysis is unreliable, and that the only reliable index of diabetic nephropathy in the rat is glomerular basement membrane thickening measured by the orthogonal intercept method on electron microscopic sections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation